When the Perpetrator Is an Educator: Assessing Justice in the Juvenile Criminal Justice System - Susanto, Maurend Benaya Immanuel; Hutabarat, Rugun Romaida (Jurnal Ilmu Hukum Kyadiren, 2025)
Sexual violence against children perpetrated by educators constitutes an egregious crime that endangers the safety and future of the nation’s youth. Although Indonesia’s special criminal law—primarily through the Child Protection Law—has established legal mechanisms for safeguarding child victims, its implementation within the judiciary remains inconsistent. This study aims to critically examine sentencing disparities in District Court Decision No. 157/Pid.Sus/2020/PN Tbn and High Court Decision No. 1271/Pid.Sus/2020/PT SBY, and to assess the extent to which the lex specialis framework is consistently applied to ensure maximum protection for child victims. Employing a normative legal approach combined with case analysis and legal document review, the study reveals inconsistencies in the imposition of criminal sanctions, including the failure to apply supplementary penalties, indicating a systemic lack of victim-centered bias in judicial decisions.